Global patterns of body size evolution in squamate reptiles are not driven by climate - Slavenko, Alex; Feldman, Anat; Allison, Allen; Bauer, Aaron Matthew; Böhm, Monika; Chirio, Laurent; Colli, Guarino R; Das, Indraneil; Doan, Tiffany M.; LeBreton, Matthew (Wiley Online Library, 2019)
Aim: Variation in body size across animal species underlies most ecological and evo‐lutionary processes shaping local‐ and large‐scale patterns of biodiversity. For well over a century, climatic factors have been regarded as primary sources of natural selection on animal body size, and hypotheses such as Bergmann’s rule (the increase of body size with decreasing temperature) have dominated discussions. However, evidence for consistent climatic effects, especially among ectotherms, remains equivocal. Here, we test a range of key hypotheses on climate‐driven size evolution in squamate reptiles across several spatial and phylogenetic scales. Location: Global. Time period: Extant. Major taxa studied: Squamates (lizards and snakes). Methods: We quantified the role of temperature, precipitation, seasonality and net primary productivity as drivers of body mass across ca. 95% of extant squamate spe‐cies (9,733 spp.). We ran spatial autoregressive models of phylogenetically corrected median mass per equal‐area grid cell. We ran models globally, across separate conti‐nents and for major squamate clades independently. We also performed species‐level analyses using phylogenetic generalized least square models and linear regressions of independent contrasts of sister species. Results: Our analyses failed to identify consistent spatial patterns in body size as a function of our climatic predictors. Nearly all continent‐ and family‐level models differed from one another, and species‐level models had low explanatory power. Main conclusions: The global distribution of body mass among living squamates varies independently from the variation in multiple components of climate. Our study, the largest in spatial and taxonomic scale conducted to date, reveals that there is little support for a universal, consistent mechanism of climate‐driven size evolution within squamates.